Keseimbangan Ketersediaan dan Kebutuhan Air Bersih serta Strategi Adaptasi Masyarakat di Kelurahan Yabansai, Kota Jayapura - Frits Kirihio; Irja Tobawan Simbiak; Sudiro Sudiro (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2026)
Households in Yabansai Urban Village, Heram District, Jayapura City, experience recurrent clean-water shortages as the Kampwolker River, the raw-water source of PDAM UPP Waena, discharges decline. This study examines the supply-demand balance of clean water and community adaptation strategies in meeting household water needs. Demand was calculated using the Directorate General of Cipta Karya (1998) standard for a subdistrict town (90-100 L/person/day). Primary data were collected through semi-structured interviews with 60 households across 12 RWs and two PDAM staff, supported by field observations of the intake, distribution network, boreholes, and household storage facilities. The results show that Yabansai's demand is 1,582,650-1,758,500 L/day, while PDAM UPP Waena's net distribution capacity is 2,268,000 L/day in the wet season and 1,008,000 L/day in the dry season. Because this capacity serves several areas, the wet-season surplus is only nominal, and the dry-season capacity is insufficient even for Yabansai alone. Despite this structural shortfall, 61.7% of respondents rate water availability as "Very Sufficient": community practices (water storage, rainwater harvesting, boreholes, water purchase) form an adaptive equilibrium that sustains daily activities but remains costly and vulnerable. The study recommends watershed rehabilitation, source diversification, distribution transparency, and network extension to unserved RWs.